Musical Sound Quality as a Function of the Number of Channels in Modern Cochlear Implant Recipients - Berg, Katelyn; Noble, Jack; Dawant, Benoit; Dwyer, Robert; Labadie, Robert; Richards, Virginia; Gifford, René (Frontiers in Neuroscience, 2019)
Objectives: This study examined musical sound quality (SQ) in adult cochlear implant (CI) recipients. The study goals were to determine: the number of channels needed for high levels of musical SQ overall and by musical genre; the impact of device and patient factors on musical SQ ratings; and the relationship between musical SQ, speech recognition, and speech SQ to relate these findings to measures frequently used in clinical protocols. Methods: Twenty-one post-lingually deafened adult CI recipients participated in this study. Electrode placement, including scalar location, average electrode-to-modiolus distance (M ̅), and angular insertion depth was determined by CT imaging using validated CI position analysis algorithms (e.g., Zhao et al., 2019; Zhao et al., 2018; Noble et al, 2013). CI programs were created using 4 – 22 electrodes with equal spatial distribution of active electrodes across the array. Speech recognition, speech SQ, music perception via a frequency discrimination task, and musical SQ were acutely assessed for all electrode conditions. Musical SQ was assessed using pre-selected musical excerpts from a variety of musical genres. Results: CI recipients demonstrated continuous improvement in qualitative judgements of musical SQ with up to 10 active electrodes. Participants with straight electrodes placed in scala tympani (ST) and pre-curved electrodes with higher M ̅ variance reported higher levels of musical SQ; however, this relationship is believed to be driven by levels of musical experience as well as the potential for preoperative bias in device selection. Participants reported significant increases in musical SQ beyond 4 channels for all musical genres examined in the current study except for Hip Hop/Rap. After musical experience outliers were removed, there was no relationship between musical experience or frequency discrimination ability and musical SQ ratings. There was a weak, but significant correlation between qualitative ratings for speech stimuli presented in quiet and in noise and musical SQ. Conclusions: Modern CI recipients may need more channels for musical SQ than even required for asymptotic speech recognition or speech SQ. These findings may be used to provide clinical guidance for personalized expectations management of music appreciation depending on individual device and patient factors.